Trisomy 18 and necrotizing enterocolitis - Alexandra Maidan; Marla A. Sacks; Steven L. Raymond; Georgi D. Mladenov; Faraz A. Khan; Andrei Radulescu (Elsevier, 2022)
Introduction: Both Trisomy 18 (T18) and Necrotizing enterocolitis totalis (NEC-T) are major causes of morbidity and mortality in neonates. However, to our knowledge there has never been a case of a full-term infant born with both T18 and NEC-T published in the literature. Case report: We present a case of NEC totalis in male neonate born at 39 weeks gestation with Trisomy 18. He was diagnosed with T18 in-utero, and after genetic counseling, the mother carried the pregnancy to term. After delivery, the newborn developed signs of respiratory distress, requiring use of continuous positive airway pressure support. On day of life (DOL) 8, multiple bloody bowel movements raised suspicion for NEC and after supplemental investigations prompted a series of exploratory laparotomies that revealed extensive necrotizing enterocolitis involving the entire gastrointestinal tract. On DOL 12, the family opted for palliative care and the patient subsequently expired. Conclusion: To our knowledge, after searching through the English literature, no cases were found showing a neonate with a combination of T18 and NEC-T.